Analisis Yuridis Penerapan UU ITE dalam Pemberantasan Ujaran Kebencian SARA di Media Sosial: Studi Putusan Nomor 949/Pid.Sus/2020/PN.Jkt.Utr - I Gede Sukadenawa Putra; Ismiyanto Ismiyanto; femmy silaswaty faried (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify and analyze the application of Article 45A paragraph (2) of the ITE Law in combating SARA hate speech on social media through a study of Decision Number 949/Pid.Sus/2020/PN.Jkt.Utr. This type of research uses normative legal research with a case approach and statutory approach. The research location focuses on court decisions and related legal materials. The data collection technique is through literature study and document analysis. Qualitative data analysis techniques are used. The results of this study show that the application of Article 45A paragraph (2) of the ITE Law faces challenges in proving elements of intent, ambiguity in legal interpretation, and technical obstacles in digital law enforcement. The court decision serves as an important precedent in affirming the boundaries between freedom of expression and hate speech. This study recommends the need to strengthen digital forensic capacity, formulate more measurable legal guidelines, and a balanced legal approach to maintain human rights and public order in digital space.